The Effect of Using Digital Children’s Literature on Storybookscanada.ca To Students’ Vocabularies at SMAN 5 Padang - Abelia Rivanka Andricos; Leni Marlina (Journal of English Language Teaching, 2023)
In learning English, mastering vocabulary is very foundational and important to have. The need to improve vocabulary can use media in the form of digital children’s literature. This study aims to find out how the effect of using digital children’s literature especially on storybookscanada.ca to students’ vocabularies at EFL secondary students. A collection of stories contained in storybookscanada.ca was used as the vocabularies enhancement treatment. This study is a quasi-experiment with a quantitative approach conducted at SMAN 5 Padang, academic year 2023/2024. The sample for this study was 33 students from XI F1 as the experimental class. Meanwhile the class used for the control group class was XI F2 with 30 students. This research results showed an increase in vocabularies owned by experimental class students. In the pre-test, the value based on the mean was 303.84 to 379.57 in post-test after the treatment. The data analysis was on sig. value 0.000 (<) 0.05. In other words, there is a significant effect on vocabularies from the use of digital children’s literature on storybookscanada.ca at SMAN 5 Padang.